An Analytical Approach for DG Placement in Reconfigured Distribution Networks - Sarfaraz Nawaz; Ajay Bansal; M. P. Sharma (International Journal of Applied Power Engineering (IJAPE), 2016)
A novel approach is proposed in this paper for optimal placement of DG units in reconfigured distribution system with the aim of reduction of real power losses while satisfying operating constraints. The proposed analytical method for optimal DG placement is developed based on a new mathematical formulation. Type-I and type-II DG units are used here. The results of the proposed technique are validated on IEEE 69 bus distribution system. The level of DG penetration is also considered in a range of 0–50% of total system load. A novel index is also proposed which incorporates level of DG penetration and percentage reduction in real power losses. The results are promising when compared with recently proposed algorithms.